Cultivating Resilience: Permaculture and Self-Sufficient Communities across European Contexts - Durán-Rubi, Elisa; Petranović, Katarina; Favoro, Angela; Hartmann, Maren; Smajlaj, Venera; Charousek, Jakub; Vovk, Ana (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
Independent living, defined as the ability to meet basic needs with autonomy and resilience, has gained popularity amid climate change, food insecurity, and energy dependence. Permaculture, a holistic design framework rooted in ecological ethics, offers practical strategies to enhance self-sufficiency while fostering community resilience. This research explores how permaculture has been developing across seven European countries (Italy, Germany, Croatia, Slovenia, Kosovo, the Czech Republic and Spain) through a comparative case study approach. Using qualitative data from literature reviews and project documentation, the research identifies key practices in food production, water and energy management, community governance, funding, theoretical framework and ecological education.